Visitor's Nature-Based Recreation Experience And Perception In Taiping Maxwell Hill - Wong, Shu Min (Universiti Malaysia Sarawak (UNIMAS), 2017)
Taiping is a heritage town in Perak and one of the attractions in Taiping is Maxwell Hill, the oldest hill resort as well as one of the popular highland destinations in Malaysia. Visitors’ nature-based recreation experience and perception are known as integral elements of visitor satisfaction study. Therefore, this study focuses on visitors’ naturebased recreation experience and perception towards Taiping Maxwell Hill. Meanwhile, researcher aims to identify the activities and facilities available in Maxwell Hill. However, study on nature and leisure experience in depth is still lacking as well as understanding the expectation of visitors is a challenging task for researcher. Researcher used the method of quantitative and qualitative to collect the data and information for this study. There are total of 188 out of 200 random respondents are achieved in the questionnaires of this study. In addition, a set of open-ended questions were prepared to Raja Nur Syamimi, the assistant manager in management office of Taiping Maxwell Hill in order to obtain additional information about Maxwell Hill. Studying visitors’ experience in terms of their perceptions is essential as the experience of visitors is the main key for management improvement in order to provide a better service for visitors.